A NOVEL TETRAZOLE ANALOGUE OF RESVERATROL IS A POTENT ANTICANCER AGENT - Bommagani, Shobanbabu (Bioorg Med Chem Lett, 2018)
A series of novel tetrazole analogues of resveratrol were synthesized and evaluated for their antileukemic activity against an extensive panel of human cancer cell lines and against the MV4-11 AML cell line. These molecules were designed as drug-like derivatives of the resveratrol analogue DMU-212 and its cyano derivatives. Four compounds 8g, 8h, 10a and 10b exhibited LD(50) values of 4.60 μM, 0.02 μM, 1.46 μM, and 1.08 μM, respectively, against MV4-11 leukemia cells. The most potent compounds, 8h and 10b, were also found to be active against an extensive panel of human hematological and solid tumor cell lines; compound 8h was the most potent compound with GI(50) values <10 nM against more than 90% of the human cancer cell lines in the 60-cell panel. Analogs 8g, 8h, 10a and 10b were also tested for their ability to inhibit the polymerization of tubulin, and compound 8h was found to be the most potent analogue. Molecular modeling studies demonstrated that 8h binds to the colchicine binding site on tubulin. Thus, compound 8h is considered to be a lead druglike molecule from this tetrazole series of compounds.